(untitled) (Research, Society and Development, 2021)
In view of the alarming number of adverse events related to medications within the scope of the Intensive Care Unit (ICU), effective actions in patient care are necessary. In this perspective, this work aims to discuss the role of nursing and pharmacy regarding the safe use of medicines, aiming to guarantee the quality of care provided to critically ill patients. An integrative review of an exploratory-descriptive character with a qualitative approach was carried out, which resulted in the selection of 21 articles, published between January and April 2021, indexed in the main databases. From the studies analyzed, it was observed that the main adverse events were related to errors in prescription, preparation and administration; occurrence of drug interactions; incompatibilities between drugs and equipment. The emergence of these problems was associated with the communication failure of the multidisciplinary team, the work overload and the lack of knowledge about the pharmacodynamics and pharmacokinetics of the drug. Therefore, it is necessary to integrate and articulate nurses and pharmacists so that pharmacotherapy is effective, safe and assertive, due to the complexity projected in practice, demanding from these professionals greater qualification and training.